Analysis of the Effects of Infusion Drips on Flow Rate and Volume Determination in IV Systems - Halid Ceylan; Ogan Karabaş; Kadri Süleyman Yiğit (Hittite Journal of Science and Engineering)

(untitled)
In this study, drop form flow examinations, which form the basis of IV applications used for therapeutic purposes, were performed. Fluid Intravenous (IV) is the practice of administering fluids into a vein. In IV applications, flow must be monitored in order to follow and control the treatment process. For this purpose, the fluid can be converted into drop form with a simple mechanism and the flow rate and volume data can be calculated by the drop counting method. Examining drop form flow processes and analyzing microdrops correctly increases the accuracy in calculating flow data and, most importantly, increases the quality of treatment in IV applications. In the scope of this study, the formation processes of microdrops and the affecting parameters were analyzed. Along with microdrop analysis, error evaluation of the drop counting method and evaluation of measurement techniques were carried out to ensure a healthy and accurate measurement process. System tests and verification were carried out with optical systems, one of the measurement techniques. As a result, this study was carried out on the importance of monitoring systems and measurement parameters in IV applications.